Taxonomy of the Triassic anomodont genus Kannemeyeria - Cruickshank, A. R. I. (Bernard Price Institute for Palaeontological Research, 1970)
The types of the species hitherto assigned to the genus Kannemeyeria Seeley 1908 have been re-examined and D. simocephalus Weithofer, D. latifrons Broom, K. proboscoides Seeley, Sagecephalus pachychynchus Jaekel and K. erithrea Haughton are synonymised as K. simocephalus (Weit). K. wilsoni Broom is retained as a monotypic species, but could be considered a female of K. simocephalus. The genus Kannemeyeria is redefined using the type of K. erithrea as a basis, as this specimen is complete, almost undistorted and comes from a reliably recorded locality, unlike the majority of other types. Kannemeyeria vanhoepeni Camp, while closely related to Kannemeyeria Simocephalus, has only one character in common with that species and is placed therefore in a new genus Proplacerias. This name is chosen because the specimen seem to have the characters which might be expected in a very early representative of the line leading to Placerias. K. argentinensis Bonaparte and K. latirostris Crozier are retained for valid reasons as separate species, occurring as they do in South America and Zambia respectively.
Main article
Keywords: Triassic; Anomodont; Kannemeyeria